Hints of auroral and magnetospheric polarized radio emission from the scallop-shell star 2MASS J05082729-2101444 - Kaur, Simranpreet; Viganò, Daniele; Béjar, Víctor J. S.; Monge, Álvaro Sánchez; Morata, Òscar; Kansabanik, Devojyoti; Girart, Josep Miquel; Morales, Juan Carlos; Anglada-Escudé, Guillem; Murgas, Felipe; Shan, Yutong; Ilin, Ekaterina; et al. (Astronomy and astrophysics, 2024)
Scallop-shell stars, a recently discovered class of young M dwarfs, show complex optical light curves that are characterized by periodic dips as well as other features that are stable over tens to hundreds of rotation cycles. The origin of these features is not well-understood. 2MASS J05082729−2101444 is a ∼25 Myr old scallop-shell star that was identified using TESS data; it has a photometric period of 6.73 h that has been attributed to rotation. Of the ∼50 recently confirmed scallop-shell stars, it is one of the few detected at radio frequencies between 1 and 8 GHz. We observed this rare system with the upgraded Giant Meterwave Radio Telescope at 575-720 MHz, covering 88% of the photometric period in each of the two observations scheduled almost a month apart in 2023. We detected approximately millijansky emission from the target in both epochs, with a significant circular polarization fraction: |V/I|∼20 − 50%. The 3.5-minute phase-folded light curves show unique variability in circular polarization. We detected an approximately hour-long helicity reversal during both epochs, and the reversals had similar amplitudes, lengths, and (possibly) occured at similar phases. These results suggest two emission components: The first is a persistent, moderately polarized component possibly ascribable to gyro-synchrotron emission driven by centrifugal breakout events. The second is a highly polarized, short burst-like component that is likely due to an electron cyclotron maser (ECM); it is indicative of auroral emission and is potentially responsible for the helicity reversal. To explain this, we discuss the different origins of the plasma responsible for the radio emission, including the possibility that the occulting material is acting as a plasma source. Future coordinated multifrequency radio and optical observations can further constrain the underlying scenario, as well as the magnetic geometry of the system, if we assume an ECM-like auroral emission.
Gesehen am 08.07.2025